Growth, Production, Nitrogen, and Chlorophyll Content of Alternanthera sissoo Propagated from Various Cutting Materials - Akib, Muh. Akhsan; Ahmad, Namrawati; Ilmi, Nur; Ibrahim, Andi (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2026)
Brazilian spinach (Alternanthera sissoo) is a leafy vegetable with nonfunctional seeds that inhibit sexual reproduction. Although vegetative propagation by cuttings is a feasible solution, information on the quality of cuttings suitable for vegetative propagation of Brazilian spinach remains limited. Therefore, research is required to determine Brazilian spinach's growth, production, and chlorophyll content from various cutting sources. The study was carried out in the screen house laboratory in Parepare City, South Sulawesi, Indonesia, from October 2023 to March 2024, using a randomized block design (RBD) with three treatments of cutting types, namely shoot cuttings (control/K1), rooted stem cuttings (K2), and stem cuttings. (K3). The data were analysed using Analysis of Variance (ANOVA) and Duncan's Test. The results showed that A. sissoo growth from cuttings consistently followed the Sigmoid growth pattern. Brazilian spinach propagated from stem cutting produced higher fresh and dry shoot weight, fresh and dry root weight, nitrogen, and chlorophyll content than those of shoot and rooted-stem cuttings. Stem cuttings likely have a more developed vascular system and greater nutrient reserves, making them more likely to develop roots successfully than other cutting materials. Furthermore, stem cuttings likely contain more carbohydrates and hormones like auxin, which promote faster root formation than shoot or rooted-stem cuttings. Stem cuttings are recommended for use in propagating Brazilian spinach.